2012
DOI: 10.1002/hbm.22015
|View full text |Cite
|
Sign up to set email alerts
|

Neural integration of speech and gesture in schizophrenia: Evidence for differential processing of metaphoric gestures

Abstract: Gestures are an important component of interpersonal communication. Especially, complex multimodal communication is assumed to be disrupted in patients with schizophrenia. In healthy subjects, differential neural integration processes for gestures in the context of concrete [iconic (IC) gestures] and abstract sentence contents [metaphoric (MP) gestures] had been demonstrated. With this study we wanted to investigate neural integration processes for both gesture types in patients with schizophrenia. During func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 74 publications
7
46
1
2
Order By: Relevance
“…These neuropsychological deficits in gesture imitation in schizophrenia have been reported by others [9,45]. Furthermore, understanding of gestures in a specific context and underlying neuronal correlates was investigated in schizophrenia patients [46,47]. The authors noted specific difficulties in gesture understanding in an abstract sentence context (metaphoric gestures).…”
Section: Discussionsupporting
confidence: 52%
“…These neuropsychological deficits in gesture imitation in schizophrenia have been reported by others [9,45]. Furthermore, understanding of gestures in a specific context and underlying neuronal correlates was investigated in schizophrenia patients [46,47]. The authors noted specific difficulties in gesture understanding in an abstract sentence context (metaphoric gestures).…”
Section: Discussionsupporting
confidence: 52%
“…Ten out of 12 participants reported decreasing reliance on English during gesture production from the first to the last session (1 reported no change, 1 did not answer the question). Interestingly, activation in the inferior frontal gyrus and middle temporal gyrus has consistently been reported during the observation of gestures (both iconic and metaphoric) [36,37]. It is interesting to note that gestures (i) appear to be strongly linked to speech [36,38,39,40,41,42] and (ii) have been shown to enhance sensorimotor representations of words.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, activation in the inferior frontal gyrus and middle temporal gyrus has consistently been reported during the observation of gestures (both iconic and metaphoric) [36,37]. It is interesting to note that gestures (i) appear to be strongly linked to speech [36,38,39,40,41,42] and (ii) have been shown to enhance sensorimotor representations of words. When combined with traditional forms of word learning, gesture-based approaches have been shown to enhance second-language acquisition [11,43].…”
Section: Discussionmentioning
confidence: 94%
“…Investigations of gesture behavior have significantly improved our understanding of social and cognitive processes (McNeill, 1992; Goldin-Meadow et al, 1993; Streek, 1994; Alibali & DiRusso, 1999), and several studies have implicated abnormal gesture behavior in schizophrenia and spectrum groups (Trosi et al, 1998; Straube et al, 2013a,b; Walther et al, 2013a,b). However, to date our understanding of gesture behavior in the psychosis risk-period has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…The field of psychosis research has prioritized the search for readily observable markers that can identify risk or elucidate pathogenic processes, leading researchers to examine gesture in patients with schizophrenia. Studies of individuals with psychosis have observed abnormal gesture activity (Troisi et al, 1998; Meilijson et al, 2004; Lavelle et al, 2013; Walther et al, 2013a;) with specific links to dysfunctional neural integration (Straube et al, 2013a), altered functional connectivity (Straube et al, 2013b), and both frontal cortex function and symptom severity (Walther et al, 2013b). Despite this growing body of evidence, and an earlier study observing gesture deficits in schizotypal personality disorder (SPD; Mittal et al, 2006), to date there have been no investigations of gesture in those at ultra high risk (UHR) for psychosis.…”
Section: Introductionmentioning
confidence: 99%